Comparative analysis of TNF-α (-308) gene polymorphism in Turkish patients with type 2 diabetes developing nephropathy and/or neuropathy - Venhar Gurbuz Can; Ozlem Cesur Gunay; Sinem Cesur (Scientific Reports)
Abstract Type 2 diabetes (T2DM) is a group of chronic and systemic metabolic diseases. Nephropathy (NP) and neuropathy (NR) are two common complications that severely affect the quality of life of patients with T2DM. In this study, our aim was to investigate the association between TNF-alpha (-308) gene polymorphism and the risk of developing NP and NR in patients with T2DM We also aimed to determine the association between TNF-alpha (-308) gene polymorphism and several demographic characteristics and biochemical parameters of patients with T2DM developed NP and/or NR. First, blood samples of patients were collected, and DNA isolation was performed. Then, real-time PCR analysis was used for genotyping the TNF-α (-308) gene utilising fluorescently labelled probes. Patients’ demographical data and biochemical parameters were also obtained. Our study did not detect any significant difference in the frequency of possessing the gene polymorphism (A allele) between the groups. Additionally, no significant difference was detected when the data on various biochemical parameters were evaluated in GG, GA, and AA genotypes.